Anaesthetic gardens. On Metaphysics by Lech Majewski - Baron, Marta (Journal of Education Culture and Society, 2020)
Interpretation of Metaphisics – the novel written by Lech Majewski, is the subject matter of theoretical, aesthetic and antropological considerations. Synthesis of arts: literature, film, painting and theatre, which occur in the novel, opens a perspective of intertextuality and provokes questions about ekphrasis, varied materials, ways of experience mediated by dispositives and reflections on humans among other problems. The crucial point in both: Majewski’s novel and this dissertation, is a triptych painted by Hieronymus Bosch – The Garden of Earthly Delight, which gradually annexes the featured world – becomes a basic figure in trying to show, how the aesthetization of reality brings Wolfgang Welsch’s cahegory of an(a)esthetics.